Accommodating succinonitrile rotators in micro-pores of 3D nano-structured cactus carbon for assisting micro-crystallite organization, ion transport and surplus pseudo-capacitance: An extreme temperature supercapacitor behavior. (10th February 2020) - Suleman, Mohd; Deraman, Mohamad; Hashmi, S.A.; Othman, M.A.R.; Kumar, Yogesh; Rajouria, S.K.; Jasni, M.R.M.
Abstract: The 3D nano-structured cactus activated carbon, AC and its composites containing 0 to 10 wt % succinonitrile, SN rotators are prepared and investigated in PVdF-HFP/Na-TFSI/EC-PC gel polymer electrolyte. Against AC, the modified porosity, micro-structure and surface chemistry for 5 wt % SN rotators in optimized AC/SN-5 electrodes leads to ∼5 times faster diffusion of ions inside pores, D ∼1.25 × 10 −4 vs. 2.50 × 10 −5  cm 2 /s, enhanced electrical conductivity, σ ∼2.36 vs. 0.76 S cm −1, meso-pores, SMESO /SMICRO  = 0.192 vs. 0.148 and surplus pseudo-capacitance. Compared with AC, the AC/SN-5 electrodes offer higher specific energy, E ∼34 vs. 20 Wh kg −1, specific power, P ∼200 vs. 40 kW kg −1, knee frequency, f k ∼25 vs. 2 Hz and specific capacitance, C s ∼244–250 vs. 145–150 F g −1 with higher retention ∼ (90 vs. 64%) at 10 A g −1 . Further, at 100 °C, contrary to AC, the AC/SN-5 electrodes can deliver a maximum power, P ∼333 vs. 66 kW kg −1 with f k ∼30 vs. 3 Hz. However, at −50 °C, reduced values of P ∼3 vs. 7 kW kg −1 and f k ∼0.5 vs. 1 Hz are observed due to death of SN rotators below – 40 °C. Graphical abstract: GAUCHE-and TRANS Conformations of SN accommodated inside Micro-Pores of AC gives AC/SN. Usual increase/decrease of IR drop with Temperature decrease/increase of AC seen in GCD curves of pristine AC at – 50 °C and +100 °C (EFFECT-1). GAUCHE CONFORM- Results in decreased Pore Depth and increased Pore Diameter (EFFECT-2). TRANS CONFORM (ROTATOR)- Results in EFFECT-2 + Enhanced Ionic Mobility due to rotator (EFFECT-3.) EFFECT-3 dominates over (EFFECT-1+EFFECT-2) at + 100 °C as seen in GCD curves of AC/SN Composite. EFFECT-1 dominates over EFFECT-2 (EFFECT-3 disappears) at – 50 °C as seen in GCD curves of AC.